(untitled) (Vietnam Journal of Community Medicine, 2026)
Aims: To evaluate the result of Pembrolizumab-containing regimens in patients with recurrent or metastatic Esophageal Cancer at Nghe An Oncology Hospital Method: A retrospective descriptive study was conducted on 19 patients with recurrent or metastatic Esophageal Cancer who received Pembrolizumab-containing regimens in Nghe An Oncology Hospital from March 2023 to May 2026 Results: The average age of 19 patients was 61,4. At the time of treatment, distant metastases were identified in 36,8% of patients. Pembrolizumab was administered as a first-line treatment in 73,7% of cases. After 6 cycles of Pembrolizumab, the disease control rate (DCR) was 71.4%, the overal response rate (ORR) was 42,8% and the median PFS was 9,2 months; The most common was neutropenia (63,2%), anemia (57,9%), most of them were grade 1, 2. Conclusion Pembrolizumab-containing regimens demonstrated clinical efficacy and acceptable toxicity in patients with recurrent or metastatic esophageal cancer.